IDENTIFIKASI AWAL PELUANG DAN TANTANGAN BUDIDAYA IKAN AIR TAWAR DI DUSUN KOKOQ LAUQ 1 DESA KELAYU SELATAN SELONG LOMBOK TIMUR - Yuliana Asri; Septiana Dwiyanti; Rangga Idris Affandi; Thoy Batun Citra Rahmadani; Muhammad Sumsanto; Laily Fitriani Mulyani; Sahrul Alim; Wastu Ayu Diamahesa; Damai Diniariwisan; Nuri Muahiddah (Universitas Mataram, 2023)
Freshwater fish farming activities in Kokoq Lauk 1 sub village have started to develop in recent years. The availability of water from the Menemeng River which passes through several sub village in the Kelayu Village, including Kokoq Lauq 1, has supported the development of freshwater fish farming activities. However, one of the main problems in aquaculture activities along this river is the decreasing water quality due to uncontrolled disposal of household waste and garbage. The decrease in water quality greatly affects the productivity of aquaculture activities such as the growth rate of fish, the survival rate and the spread of disease in the cultivated fishes. This activity is an initial identification of opportunities and challenges in the development of freshwater fish farming in Kokoq Lauk 1. The results of this initial study will be used as recommendations for further community service activities.